PENGEMBANGAN MULTIMEDIA PEMBELAJARAN PEMBUATAN FASHION BLOG - Arin Isti Fadah; Suciati Suciati (Universitas Pendidikan Indonesia, 2016)
The main problems in Publications Mode subjects is still very limited media publications learning mode that apply information and communication technologies, especially in the form of fashion blog. The research objective in general is to create guidelines for how to create a fashion blog in the form of multimedia, which is useful as a medium of learning that is interactive and interesting so the students will be more active and independent in understanding learning. The method used is the Research and Development (R D) through the stages of analysis, design, development, implementation, and evaluation of multimedia. Results of the validation of multimedia learning making of fashion blogs shows that multimedia created can be used, with an average percentage of 88.13% of the feasibility of materials experts, 94.52% of the multimedia experts, and 94.38% of the users, so it can be described that standard feasibility of developed multimedia is including in the excellent category. This multimedia can be implemented in the learning mode fashion publications and blogs, and can be more developed in similar research.